Membangun Citra Sekolah Berdasarkan Marketing Mix untuk Meningkatkan Jumlah Peserta Didik - Basuki Budiyatmo; Ade Iriani (Kelola: Jurnal Manajemen Pendidikan, 2022)
This study aims to obtain the potential of schools in each marketing mix variable to build the image of the school in order to increase the number of students at SMP Kristen Krida Wacana Sragen. This research uses a descriptive qualitative method. Collecting data through interviews, observations, and documentation studies. The data analysis technique uses the Miles and Huberman model (interaction model). Data validation with source triangulation and technical triangulation. The results of the research show 1. Building the image of the school to increase the number of students is carried out in fellowship activities and meetings both in the church environment, Christian student associations, and Christian religious teacher meetings, by introducing the advantages of the school. Promotion through the distribution of brochures and banners, presentations at churches, door-to-door/visits to prospective students, and social media. 2. Weaknesses and obstacles in building a school's image include not having a planned and systematic program, not having a public relations department, every promotion is not well documented, not having a special promotion team, schools targeted for promotion being limited, promotional content lacks appeal, costs promotion is limited, human resources are limited, communication with the church is less intense, there is no new form of promotion, committee, and foundations are less actively involve the d in promotion, and teachers are less active in building an image with infectious messages. 3. The implications of the marketing mix in building the image are a) product in the form of superior choir extracurricular programs, b) price, maintaining current prices, strengthened in seeking sponsors and donors, c) Place, improving the environment/classroom where teaching and learning activities are conducted, d) promotion, planning good promotions, building partnerships, and looking for uniqueness or differentiation, e) people, improving performance, building communication, school image culture, forming a public relations department f) physical evidence, improving infrastructure in the form of environmental management, painting, making schools green, and improving the appearance of the front facing the highway g) Process, service improvement and implementation of supervision by the principal in a good and planned manner.